Aligning manufacturing capabilities with business strategy: an empirical study in high-tech industry. (1st January 2002) - Chang, Shih-Chia; Lin, Neng-Pai; Wea, Chi-Lin; Sheu, Chwen
Previously suggested frameworks for business strategies failed to consider the relationship between manufacturing capabilities and business strategies. Based on observations from high-tech industry, this study proposes a new business strategy framework, taking manufacturing capabilities into consideration. This new framework categorises business strategy types into: Pre-emptive/First Mover strategy, Low Cost/Follower strategy and Differentiation/Follower strategy. Data were collected from 113 high-tech manufacturing firms in Taiwan to validate this model. Statistical results indicate that the compatibility between business strategy and manufacturing capabilities is important to a firm's performance in new product introduction, net profit and sales. Our findings could serve as guidelines for firms in developing their business strategy. Specifically, firms should invest resources and time to develop a set of manufacturing capabilities to fit into their business strategies.